Pendidikan Kesetaraan Gender dalam Perspektif Al-Qur’an - Aufa Fatchia Rahma (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This article explores gender equality education through a Qur’anic perspective as a response to the ongoing reality of gender inequality in Muslim societies and Islamic educational settings. The study focuses on understanding how gender equality is framed in social discussions, how the Qur’an conveys principles of equality in its verses, and how these principles can be applied within Islamic education. Using a qualitative library-based approach, the research examines relevant Qur’anic passages, interpretations from both classical and contemporary scholars, as well as recent academic literature. The findings indicate that the Qur’an upholds equal human dignity, moral accountability, and spiritual worth for men and women alike, placing faith and righteous conduct above gender as the measure of merit. The persistence of gender inequality is largely rooted in patriarchal cultural norms and partial interpretations, rather than in the core teachings of the Qur’an. In this context, Islamic education holds a crucial role in promoting gender justice by incorporating inclusive interpretations and reinforcing Qur’anic values of equality, justice, and social responsibility.